Correction to: Observations on the May 2019 Joffre Peak landslides, British Columbia - Pierre Friele; Tom H. Millard; Andrew Mitchell; Kate E. Allstadt; Brian Menounos; Marten Geertsema; John J. Clague (Landslides, 2020)
The article “ Observations on the May 2019 Joffre Peak landslides, British Columbia ”, written by Pierre Friele, Tom H. Millard, Andrew Mitchell, Kate E. Allstadt, Brian Menounos, Marten Geertsema and John J. Clague , was originally published electronically on the publisher’s internet portal (currently SpringerLink) on January 2020 without open access.